Physio-Morphological, Biochemical and Transcriptomic Analyses Provide Insights Into Drought Stress Responses in Mesona chinensis Benth - Tang, Danfeng; Quan, Changqian; Lin, Yang; Wei, Kunhua; Qin, Shuangshuang; Liang, Ying; Wei, Fan; Miao, Jianhua (Frontiers in Plant Science, 2022)
Drought stress affects the normal growth and development of Mesona Chinensis Benth (MCB), which is an important medicinal and edible plant in China. To investigate the physiological and molecular mechanisms of drought resistance in MCB, different concentrations of polyethylene glycol 6000 (PEG6000) (0, 5%, 10%, 15%) were used to simulate drought conditions in this study. Results showed that the growth of MCB was significantly limited under drought stress conditions. Drought stress induced the increases in the contents of Chla, Chlb, Chla+b, soluble protein, soluble sugar, and soluble pectin and the activities of SOD, CAT, TAC, H2O2, and MDA. Transcriptome analysis revealed 3494 differentially expressed genes (DEGs) (1961 up-regulated and 1533 down-regulated) between the control and 15% PEG6000 treatments. These DEGs were identified to be involved in the 10 metabolic pathways, including “plant hormone signal transduction”, “brassinosteroid biosynthesis”, “plant-pathogen interaction”, “MAPK signaling pathway-plant”, “starch and sucrose metabolism”, “pentose and glucuronate interconversions”, “phenylpropanoid biosynthesis”, “galactose metabolism”, “monoterpenoid biosynthesis”, and “ribosome”. In addition, transcription factors (TFs) analysis showed 8 out of 204 TFs, TRINITY_DN3232_c0_g1 (ABA-responsive element (ABRE)-binding transcription factor1, AREB1), TRINITY_DN4161_c0_g1 (auxin response factor, ARF), TRINITY_DN3183_c0_g2 (abscisic acid-insensitive 5-like protein, ABI5), TRINITY_DN28414_c0_g2 (ethylene-responsive transcription factor ERF1b, ERF1b), TRINITY_DN9557_c0_g1 (phytochrome-interacting factor, PIF3), TRINITY_DN11435_c1_g1, TRINITY_DN2608_c0_g1, and TRINITY_DN6742_c0_g1, were closely related to the “plant hormone signal transduction” pathway. Taken together, it was inferred that these pathways and TFs might play important roles in response to drought stress in MCB. The current study provided important information for MCB drought resistance breeding in the future.